Juegos Tradicionales Wayúu Como Estrategia en los Procesos Atencionales en Estudiantes de Cuarto y Quinto Grado. (2022)
The author of this study recognizes in traditional games a tool that can be used not only by teachers, but also by parents and the community in general to improve attention and concentration and thus optimize learning processes in children and in families. girls. That is why the general objective of this study was to propose an intervention based on traditional Wayúu games to strengthen the attentional process in fourth and fifth grade students of the Mini Mundo de Riohacha La Guajira institution, for this, we worked under a qualitative, phenomenological, non-experimental methodology, which had a total of 5 participants, to whom a semi-structured interview was applied that allowed establishing as results that in the Wayuu community the traditional games are similar to those of the arijunas, within which stand out mainly: The spinning top or "chocho", bowling, stone throwing and one very typical of the culture, La Wayuunkerra (clay doll) and that the games are limited to a tool to entertain students and children. concludes that, under the perception of the professionals, it is important to vary the games, however, some children need more interventions than others taking into account the special needs of each one, for example children with attentional difficulties, low cognitive capacity, and intellectual disability. Finally, the author of this study considers it important to mention that throughout the research process there were bibliographic limitations, since no evidence was found of studies focused on traditional games to improve processes in indigenous communities.